2015
DOI: 10.1038/srep16791
|View full text |Cite|
|
Sign up to set email alerts
|

CpG island erosion, polycomb occupancy and sequence motif enrichment at bivalent promoters in mammalian embryonic stem cells

Abstract: In embryonic stem (ES) cells, developmental regulators have a characteristic bivalent chromatin signature marked by simultaneous presence of both activation (H3K4me3) and repression (H3K27me3) signals and are thought to be in a ‘poised’ state for subsequent activation or silencing during differentiation. We collected eleven pairs (H3K4me3 and H3K27me3) of ChIP sequencing datasets in human ES cells and eight pairs in murine ES cells, and predicted high-confidence (HC) bivalent promoters. Over 85% of H3K27me3 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 57 publications
7
30
0
1
Order By: Relevance
“…Although often associated with promoter hypermethylation, polycomb-mediated gene silencing may occur independent of DNA methylation (86,87), typically in the context of bivalent chromatin, exhibiting occupancy of PcG proteins and simultaneous activation (H3K4Me3) and repressive (H3K27Me3) histone marks. Frequently observed in stem cells, bivalent chromatin maintains differentiation-related genes in a repressed, but poised state for rapid activation or permanent silencing depending on the differentiation signal (88,89 (90). Collectively, these experiments were the first demonstration that EZH2 is over-expressed in MPM, and that PRC-2 is a potential therapeutic target in these neoplasms.…”
Section: Polycomb Mediated Gene Silencingmentioning
confidence: 76%
“…Although often associated with promoter hypermethylation, polycomb-mediated gene silencing may occur independent of DNA methylation (86,87), typically in the context of bivalent chromatin, exhibiting occupancy of PcG proteins and simultaneous activation (H3K4Me3) and repressive (H3K27Me3) histone marks. Frequently observed in stem cells, bivalent chromatin maintains differentiation-related genes in a repressed, but poised state for rapid activation or permanent silencing depending on the differentiation signal (88,89 (90). Collectively, these experiments were the first demonstration that EZH2 is over-expressed in MPM, and that PRC-2 is a potential therapeutic target in these neoplasms.…”
Section: Polycomb Mediated Gene Silencingmentioning
confidence: 76%
“…This enrichment was much stronger than for the ChIP bound targets of Cbx7 (p < 10 −5 ). Cbx7 is a part of the PRC complex, which binds predominantly at bivalent chromatin at promoters of transcription regulators in ES cells (Mantsoki et al, 2015).…”
Section: Development and Validation Of An Adaptivementioning
confidence: 99%
“…Computational analysis of the dataset from different ChIP-seq experiments also showed that genome-wide locations of PRC1 and PRC2 complexes can be successfully predicted with the use of mapping locations sizes of CpG islands in parallel with different activator motifs. The main conclusion was that large CpG islands depleted of activating motifs are bound by both PRC complexes in pluripotent stem cells [204,207]. In more recent studies bivalent domains were connected to different nucleosome remodeling complexes too (reviewed in [211]).…”
mentioning
confidence: 98%
“…These bivalent markings suggest that certain genes are poised for both activation and repression in stem cells [204,207]. Serine 2 phosphorylation of RNA polymerase II is present in the coding regions of the active genes, but it is absent from paused and poised complexes.…”
mentioning
confidence: 99%
See 1 more Smart Citation